Heat management in integrated circuits on-chip and system-level monitoring and cooling - Ogrenci-Memik, Seda (The Institution of Engineering and Technology, 2015)
The book comprises 6 chapters and covers the following topics: heat in integrated circuits and systems; on-chip temperature sensing; dynamic thermal management; active cooling; mitigating thermal events at the system level and above; and emerging directions in thermal aware systems.